2009
DOI: 10.1111/j.1553-2712.2009.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Adjusting the Threshold of the Quantitative D‐dimer Based on Pretest Probability of Acute Pulmonary Embolism

Abstract: Objectives: The utility of D-dimer testing for suspected pulmonary embolism (PE) can be limited by test specificity. The authors tested if the threshold of the quantitative D-dimer can be varied according to pretest probability (PTP) of PE to increase specificity while maintaining a negative predictive value (NPV) of >99%.Methods: This was a prospective, observational multicenter study of emergency department (ED) patients in the United States. Eligible patients had a diagnostic study ordered to evaluate possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
3
28
1
1
Order By: Relevance
“…Several studies have compared clinical gestalt assessment to the Wells score and have found comparable results in assessing pretest probability. 19–21 Moreover, some clinicians may err on the side of ordering unnecessary CT-PA in low-risk patients for fear of litigation. Runyon et al demonstrated that only half of physicians who are familiar with commonly used clinical decision rules use them in more than half of appropriate patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared clinical gestalt assessment to the Wells score and have found comparable results in assessing pretest probability. 19–21 Moreover, some clinicians may err on the side of ordering unnecessary CT-PA in low-risk patients for fear of litigation. Runyon et al demonstrated that only half of physicians who are familiar with commonly used clinical decision rules use them in more than half of appropriate patients.…”
Section: Discussionmentioning
confidence: 99%
“…123, 124 Our study makes no assumption about the “correct” frequency of D-dimer use. D-dimer use is explicitly considered in the model through the estimation of costs and health outcomes for different D-dimer cutoffs in the setting of different Wells patient categories.…”
Section: Discussionmentioning
confidence: 99%
“…Using the combination of low clinical risk and higher d-dimer threshold could have prevented a CTA study in 1/3 of all patients. Kabrhel et al observed that for a large population of patients at low clinical risk for pulmonary embolism (prevalence of 2.9%), doubling the d-dimer threshold for any quantitive d-dimer assay resulted in a significant increase in specificity from 63% to 86% without a significant decrease in the negative predictive value (99.6% to 98.9%) [27].…”
Section: Discussionmentioning
confidence: 99%